Assessment of dual-energy computed tomography derived virtual monoenergetic imaging for target volume delineation of brain metastases. - Kraft, Johannes; Lutyj, Paul; Grabenbauer, Felix; Ströhle, Serge Peer; Tamihardja, Jörg; Razinskas, Gary; Weick, Stefan; Richter, Anne; Huflage, Henner; Wittig, Andrea; Flentje, Michael; Lisowski, Dominik (Radiotherapy and Oncology, 2023)
BACKGROUND: Objective and subjective assessment of image quality of brain metastases on dual-energy computed tomography (DECT) virtual monoenergetic imaging (VMI) and its impact on target volume delineation. MATERIALS AND METHODS: 26 patients with 37 brain metastases receiving Magnetic Resonance Imaging (MRI) and DECT for stereotactic radiotherapy planning were included in this retrospective analysis. Lesion contrast (LC), contrast-to-noise ratio (CNR) and signal-to-noise ratio (SNR) were assessed for reconstructed VMI at 63 keV and artificial 120 kV Computed Tomography (CT). Image contrast and demarcation of metastases between 120 kV CT, VMI and MRI were subjectively assessed. Brain metastases were delineated by four radiation oncologists on VMI with a fixed or free brain window and contours were compared to solely MRI-based delineation using the Dice similarity coefficient. RESULTS: LC, CNR and SNR were significantly higher in VMI than in 120 kV CT (p < 0.0001). Image contrast and lesion demarcation were significantly better on VMI compared to 120 kV CT (p < 0.0001). Mean gross tumor volume (GTV)/planning target volume (PTV) Dice similarity coefficients were 0.87/0.9 for metastases without imaging uncertainties (no artifacts, calcification or impaired visibility with MRI) but worse for metastases with imaging uncertainties (0.71/0.74). Target volumes delineated on VMI were around 5-10% smaller compared to MRI. CONCLUSION: Image quality of VMI is objectively and subjectively superior to conventional CT. VMI provides significant advantages in stereotactic radiotherapy planning with improved visibility of brain metastases and geometrically distortion-free representation of brain metastases. Beside a plausibility check of MRI-based target volume delineation, VMI might improve reliability and accuracy in target volume definition particularly in cases with imaging uncertainties with MRI.
EVALuna2:557932